VERBAL AND NON-VERBAL COMMUNICATION IN TEACHER TALK IN THE CLASSROOM UNIVERSITAS MUSLIM MAROS - Nuraeni Nuraeni; Isnaeni Wahab (SELTICS, 2020)
This research aimed to analyze the forms of verbal and nonverbal communication in teacher talk. The method used in this research was descriptive qualitative. The instrument of the study was the FLINT System and Darn classification. The participants of this research were the teacher and students in a speaking class of the English Department. The results show that teacher talk gives a positive impact on students’ performance. During the class interaction, the teacher successfully met the aspects of good teacher talk and applied some forms of FLINT system of verbal communication and some elements of non-verbal communication. For the FLINT system, the teacher applied to ask questions, giving encouragement, giving direction, critiquing students’ behavior, dealing with feelings and, prising. For the form of nonverbal communication, the teacher applied only two forms, those are kinesics which is referred to as gestures, and haptics is referred to as touching.